Variability in agricultural productivity and rural household consumption inequality: Evidence from Nigeria and Uganda - Amare, Mulubrhan; Shiferaw, Bekele; Takeshima, Hiroyuki; Mavrotas, George (Wiley, 2021)
This paper uses multiple rounds of panel data to assess the distributional implications of the variability in agricultural productivity in Nigeria and Uganda. It uses both a conventional decomposition and a regression‐based inequality decomposition approach to estimate the impact of climate‐induced variability in agricultural productivity. To mitigate the endogeneity associated with unobserved time‐invariant and time‐variant household fixed effects, we use rainfall shocks as a proxy for estimating the exogenous variability in agricultural productivity that affects consumption. Results suggest that a 10% increase in the variability of agricultural productivity tends to decrease household consumption by 38 and 52% on average for Nigeria and Uganda, respectively. Controlling for other factors, variability in agricultural productivity contributed to between 25% and 43% of consumption inequality between 2010 and 2015 for Nigeria; and 16% and 31% of consumption inequality between 2009 and 2011 for Uganda. We also show that variability in agricultural productivity increases changes in consumption inequality over time.